Development and validation of a RP- HPLC method for the quantitation studies of bromadiolone in Ratitox F - Elena Gabriela Oltean; Nica, A. (Medicamentul Veterinar)
An isocratic high-performance liquid chromatography (HPLC) procedure was developed for the quantitative determination of bromadiolone (hydroxycoumarins) in Ratitox F product – rodenticide. HPLC separation was carried out by reversed phase chromatography ODS 2 Hypersil C18 (250 mm x 4.6 mm i.e.; 5 ìm particle size), held in thermostat at 25°C. The mobile phase consisted of methanol/0.1% aqueous solution phosphoric acid (90/10v/v), with a flow rate of 1 ml/min and with UV detection at 265 nm. In order to validate the method, the following parameters have been investigated- linearity (r2 = 0.9999), range, precision, accuracy, specificity, limit of detection and limit of quantification. The described method can be successfully applied for the analysis of Ratitox F – rodenticide.